Is carpal tunnel decompression warranted for HNPP?. Issue 4 (December 2013) - Earle, Nicholas; Zochodne, Douglas W.
Abstract The role of carpal tunnel decompression surgery for patients that have hereditary neuropathy with liability to pressure palsy (HNPP) is currently unknown. Since recovery from carpal tunnel compression is often associated with remyelination or nodal reconstruction rather than axonal regeneration, it is uncertain whether the PMP22 deletion associated with HNPP interrupts myelin or nodal reconstitution. We describe two patients with genetically confirmed HNPP and symptomatic carpal tunnel syndrome that had clinical and electrophysiological improvement after surgical decompression. The findings indicate a capacity for conduction repair in HNPP. They also suggest a need for further investigation and discussion around whether to offer carpal tunnel decompression to symptomatic HNPP patients.